Cell-free biosynthesis and engineering of ribosomally synthesized lanthipeptides - Liu, Wan-Qiu; Ji, Xiangyang; Ba, Fang; Zhang, Yufei; Xu, Huiling; Huang, Shuhui; Zheng, Xiao; Liu, Yifan; Ling, Shengjie; Jewett, Michael C.; Li, Jian (Nature communications, 2024)
Ribosomally synthesized and post-translationally modified peptides (RiPPs) are a major class of natural products with diverse chemical structures and potent biological activities. A vast majority of RiPP gene clusters remain unexplored in microbial genomes, which is partially due to the lack of rapid and efficient heterologous expression systems for RiPP characterization and biosynthesis. Here, we report a unified biocatalysis (UniBioCat) system based on cell-free gene expression for rapid biosynthesis and engineering of RiPPs. We demonstrate UniBioCat by reconstituting a full biosynthetic pathway for de novo biosynthesis of salivaricin B, a lanthipeptide RiPP. Next, we delete several protease/peptidase genes from the source strain to enhance the performance of UniBioCat, which then can synthesize and screen salivaricin B variants with enhanced antimicrobial activity. Finally, we show that UniBioCat is generalizable by synthesizing and evaluating the bioactivity of ten uncharacterized lanthipeptides. We expect UniBioCat to accelerate the discovery, characterization, and synthesis of RiPPs. Ribosomally synthesized and post-translationally modified peptides (RiPPs) are a major class of natural products with potent biological activities but a vast majority of RiPP gene clusters remain unexplored in microbial genomes. Here, the authors report a unified biocatalysis (UniBioCat) system based on cell-free gene expression for rapid biosynthesis and engineering of RiPPs.